Genetic and morphological characterisation of the Ankole Longhorn cattle in the African Great Lakes region - Ndumu, D.; Baumung, R.; Hanotte, Olivier H.; Wurzinger, Maria; Okeyo Mwai, Ally; Kibogo, H.; Sölkner, Johann; Han Jianlin (Springer, 2008)
The study investigated the population structure, diversity and differentiation of almost all of the ecotypes representing the African Ankole Longhorn cattle breed on the basis of morphometric (shape and size), genotypic and spatial distance data. Twentyone morphometric measurements were used to describe the morphology of 439 individuals from 11 sub-populations located in five countries around the Great Lakes region of central and eastern Africa. Additionally, 472 individuals were genotyped using 15 DNA microsatellites. Femoral length, horn length, horn circumference, rump height, body length and fore-limb circumference showed the largest differences between regions. An overall FST index indicated that 2.7% of the total genetic variation was present among sub-populations. The least differentiation was observed between the two sub-populations of Mbarara south and Luwero in Uganda, while the highest level of differentiation was observed between the Mugamba in Burundi and Malagarasi in Tanzania. An estimated membership of four for the inferred clusters from a model-based Bayesian approach was obtained. Both analyses on distance-based and model-based methods consistently isolated the Mugamba sub-population in Burundi from the others.